University-Industry Collaboration in Innovation: Extent of Students’ Engagement in South East, Nigeria - James Akal-karali Obineche; Marycynthia Chetachukwu Obineche; Peter I. Okoye (Journal of Research in Industrial Technology and Educational Studies, 2026)
Following the observed low employability skills among Nigerian graduates, the need to assess the extent of engagement of the students in the labour needed skills becomes important. This study therefore focused on university-industry collaboration in innovation and the extent to which students are engaged in Nigeria. The study was delimited to Federal and State universities; all registered automobile production companies in South East, Nigeria. Five research questions guided the study while three hypotheses were tested. The study adopted descriptive survey design. A total of 333 participants were studied. A multi-stage sampling technique was employed in selecting respondents for the study. First, purposive sampling was used to select universities and automobile industries known to have existing collaboration arrangements. Second, stratified sampling was applied to categorize respondents into three strata: students, university staff, and industry personnel. Finally, simple random sampling was used within each stratum to select participants proportionately. The primary instrument for data collection was a structured questionnaire developed by the researcher. The instrument was structured using a 5-point Likert scale to measure respondents’ perceptions. The questionnaire was reviewed by three experts each from educational management, industrial technology education and automobile industries. A pilot study was conducted using a small sample of respondents from Delta State University Abraka and God is Good auto industries respectively. Data obtained from the pilot test were analyzed using Cronbach’s Alpha to a reliability coefficient of 0.70, 80, 72, 74 and 81 and were considered acceptable for the study. Questionnaires were administered physically and electronically and data collected were analyzed using mean and standard deviation to answer the research questions while ANOVA was used to test the hypothesis. Based on the findings of this study, it was concluded that the extent of students’ engagement in university–industry collaboration in innovation in South East Nigeria is low and therefore recommends improved university-industry innovation collaboration to enhance graduates’ employability.